2020
DOI: 10.3390/metabo10030086
|View full text |Cite
|
Sign up to set email alerts
|

Local Phenomena Shape Backyard Soil Metabolite Composition

Abstract: Soil covers most of Earth’s continental surface and is fundamental to life-sustaining processes such as agriculture. Given its rich biodiversity, soil is also a major source for natural product drug discovery from soil microorganisms. However, the study of the soil small molecule profile has been challenging due to the complexity and heterogeneity of this matrix. In this study, we implemented high-resolution liquid chromatography–tandem mass spectrometry and large-scale data analysis tools such as molecular ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…Studies of the metabolites produced by plant-associated microbiomes in situ are still limited and complex owing to the dynamics and heterogeneity of the soil environment. Soil metabolites are composed of both plant and microbial secreted molecules and their production is influenced by the soil properties and by the interactions of soil microorganisms with host plants (Pétriacq et al, 2017;Mhlongo et al, 2018;Hayden et al, 2019;Jacoby and Kopriva, 2019;Nguyen et al, 2020). Moreover, recent studies have also been using new approaches to study soil metabolites.…”
Section: Current-omics and Other Approaches For Studying The Plant MImentioning
confidence: 99%
“…Studies of the metabolites produced by plant-associated microbiomes in situ are still limited and complex owing to the dynamics and heterogeneity of the soil environment. Soil metabolites are composed of both plant and microbial secreted molecules and their production is influenced by the soil properties and by the interactions of soil microorganisms with host plants (Pétriacq et al, 2017;Mhlongo et al, 2018;Hayden et al, 2019;Jacoby and Kopriva, 2019;Nguyen et al, 2020). Moreover, recent studies have also been using new approaches to study soil metabolites.…”
Section: Current-omics and Other Approaches For Studying The Plant MImentioning
confidence: 99%
“…The soil extract contained >1000 potential chemical features as determined by LC-MS that occurred in a wide range of concentrations (data not shown). 41 Two DNA intercalators, 1 and 2, were spiked into the soil extract in low concentrations [1:1:600 (w/w/w), respectively] to test the robustness of the assay. Analysis revealed that even under those challenging conditions both compounds were readily detected (Figure 5), affording confidence that LLAMAS could be expected to function even in cases presenting extreme levels of chemical complexity.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…We employed a potential “worst-case” scenario that consisted of an organic extract prepared from soil (the top ∼7 cm of material collected from a low-lying hardwood forest plot that supported lush herbaceous plant growth). The soil extract contained >1000 potential chemical features as determined by LC-MS that occurred in a wide range of concentrations (data not shown) . Two DNA intercalators, 1 and 2 , were spiked into the soil extract in low concentrations [1:1:600 (w/w/w), respectively] to test the robustness of the assay.…”
Section: Resultsmentioning
confidence: 99%
“…Assessing soil organic matter features under drought and normal conditions using direct infusion high resolution mass spectrometry and LC-MS/MS feature based molecular networking NICOLE DIDONATO 1 , ALBERT RIVAS UBACH 1 , CHAEVIEN CLENDINEN 1 , NOAH SOKOL 2 , NIKOLA TOLIC 1 , DINESH ADHIKARI 2 , CARMEN ENID MARTINEZ 3 , JENNIFER PETT-RIDGE 2 AND LJILJANA PASA TOLIC 1 1 Pacific Northwest National Laboratory 2 Lawrence Livermore National Laboratory 3 Cornell University Presenting Author: nicole.didonato@pnnl.gov Knowledge of the type of carbon that escapes mineralization and persists in soils is important for predicting carbon fluxes in a warming climate. Direct infusion FTICRMS enables observations of broad differences in compositions of soil organic matter molecular formulas among treatments 1 .…”
mentioning
confidence: 99%
“…Although complete separation of soil organic matter is not yet achievable, LC-MS/MS compliments direct infusion by reducing charge competition, improving feature detection and allowing for molecular identification 2 . However, only a fraction of soil organic matter features can be identified due to the lack of comprehensive libraries 3 . Molecular networking can further improve identifcation of unknown compounds by matching their fragmentation spectra with similar spectra of known compounds.…”
mentioning
confidence: 99%